Fate and risks of potentially toxic elements associated with lacustrine groundwater discharge: quantification, modeling, and biogeochemistry - Shen Qu; Juliang Wang; Keyi Zhang; Mengyu Fan; Yuanzhen Zhao; Xu Yang; Zhongli Wang; Helena I. Gomes; Rachel L. Gomes; Limin Duan; Shaogang Dong; Ruihong Yu (Environment International, 2025)
While potentially toxic elements (PTE) in lake have been widely studied, their enrichment, fate and health risks associated with lacustrine groundwater discharge (LGD) remain poorly understood. Thus, self-organizing maps (SOM) and positive matrix factorization (PMF) were employed in present work to decipher source of selected PTE (Li, V, Mn, Cr, Co, Ni, Cu, Zn, Ba, Pb, U, Sr) in Ulansuhai Lake basin (Inner Mongolia, China). On this basis, multi-isotopic tracers (δD/δ18Owater, 87Sr/86Sr, δ34S/δ18Osulfate, 222Rn) were used to indicate the geochemical processes related to PTE enrichment and fate. Groundwater exhibited higher PTE concentrations than surface waters, with Mn levels 230-fold higher (0.575 vs. 0.003 mg/L), while Cr, Ni, Zn, and Ba showed 2-, 2.2-, 3-, and 1.5-fold increases, respectively. 68 samples were grouped to four clusters (C1-C4) and characterized by a hazard gradient of C4 > C3 > C1 > C2. Quantitative source apportionment identified evaporite dissolution (46.2 %) as the dominant PTE contributor, followed by industrial (23.1 %) and redox processes (23.9 %), with minor agricultural inputs (6.8 %). LGD-mediated fluxes, particularly Mn (1.71 ± 0.05 mg/m2/d) and Sr (8.63 ± 0.23 mg/m2/d), substantially influenced lake water quality. Microbial analysis revealed higher diversity (ace index = 1751 ± 577) in groundwater, while surface water PTE had a more pronounced impact on microbial functionality than groundwater (p < 0.001). Health risk assessment demonstrated elevated hazards in PTE contaminated groundwater, posing higher non-carcinogenic (non-carcinogenic risk-HI: 1.43 vs 1.25) and carcinogenic risks (carcinogenic risk assessment-CR: 0.005 vs 0.003) than surface water, with children being more vulnerable (5, 8 and 7 cases per 1000 children were found at carcinogenic risk). This multi-method investigation elucidates LGD-driven PTE cycling fluxes and mechanisms, providing critical insights for groundwater-lake management.